Compadrazgo y reciprocidad en los andes colombianos: El caso de gualmatán (nariño). Colombia (2016)
The article presents the institution of compadrazgo as a coping strategy that allowed the contractual exchange market from establishing and strengthening relations of production based on reciprocity, which are based on a moral obligation. Through ethnographic work in Gualmatan compadrazgos types, ways of their establishment and their relationship with the Andean reciprocity described. However, as a result of the modernizing process of agrarian change, today the institution of compadrazgo begins to crumble. For that reason, finally it analyzes the transformation and adaptation of compadrazgo to new social contexts.